(untitled) (Research, Society and Development, 2022)
This study, whose project was approved by the Ethics Committee for Research with Human Beings of the Estácio de Sá de Santa Catarina University Center, takes as its object of study the development aspects of the professional training of literacy teachers based on the National Pact for Literacy in Age Certain (PNAIC). The objective is to analyze the contributions that the program’s continuing education provides to literacy teachers in the early years of Elementary School in terms of their professional development and teaching practices of reading and writing. Therefore, the contributions of Imbernón, Nóvoa, Ferreira and Leal, Kramer, Soares and Vigotski, among others, were sought as a theoretical framework. The research was carried out in a state elementary school in the city of São José/SC with 08 participants, 06 teachers and 02 pedagogical coordinators. We opted for an exploratory qualitative approach and, thus, semi-structured interviews were carried out as investigation devices. Enabled and supported the re-signification of their practices in the discussions of the challenges and difficulties encountered in their practice, mainly with first-year classes. The PNAIC training course can be considered, therefore, as a successful training action, which brings contributions and impacts on the professional development of literacy teachers and on their teaching practices of reading and writing in the early years of Elementary School.